Music Center In Banda Aceh, Theme : Expressionist Architecture - haji, Iwan; Aini, Qurratul (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2024)
The city of Banda Aceh quite regularly holds music events ranging from small to large scale. The city of Banda Aceh does not yet have music center facilities capable of accommodating the enthusiasm of music lovers. Usually musical activities are often held in the Blang Padang field, the Arts and Culture Park Building, and Ratu Safiatuddin Park. The main objective of building a Music Center Building in Banda Aceh is to provide a music center building in Banda Aceh with adequate facilities. This Music Center is located in the trade and services area located on Jl. Prof. Ali Hasyimi, Pango, District. Ulee Kareng, Banda Aceh City. The design approach uses the theme of Expressionist Architecture, the form displays the expression of a musical note from the song Bungong Jeumpa, the shape of the building is made to follow an up and down pattern with a play in the form of dynamic curved lines, the color of the building shows the expression of the Bungong Jeumpa flower white.The results of this design apply a single mass pattern, with a building of 3 floors, a land area of ​​30,237 m² (3,237 Ha). The ground floor area is 21,165 m², the overall floor area is 105,829 m², and the minimum GSB is 10 m. The facilities are an Auditorium with a capacity of 1200 spectators, 2 Music Studio Rooms, 2 Classrooms, Music Gallery, Retail and supporting rooms such as: Management Room, Library, and other supporting facilities such as: Prayer room, Cafe, Waiting Room, Lavatory, and Security Post .